Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2478/s13380-014-0222-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular drug targets and therapies for Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder that is characterized by normal memory loss and cognitive impairment in humans. Many drug targets and disease-modulating therapies are available for treatment of AD, but none of these are effective enough in reducing problems associated with recognition and memory. Potential drug targets so far reported for AD are β-secretase, γ-secretase, amyloid beta (Aβ) and Aβ fibrils, glycogen synthase kinase-3 (GSK-3), acyl-coenzyme A: cholesterol acyl-transferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 141 publications
0
9
0
Order By: Relevance
“…Air pollution exposure especially damages the BBB in the brainstem and can trigger an autoimmune response contributing to the neuroinflammatory and AD pathology present in children from very large urban centers (Calderón-Garcidueñas et al, 2015; Brockmeyer and D’Angiulli, 2016). Even though numerous studies connect specific metals and metalloids with Aβ and tau pathology (e.g., Aβ spontaneously self-aggregates in the presence of divalent metals like Fe, Cu, and Zn into amyloid fibrils, Mandel et al, 2007), recently bringing a “metal hypothesis of AD” into focus (Bush and Tanzi, 2008; Bush, 2013; Singh et al, 2014), such data remain rather controversial, warranting further investigations until convincing conclusions might be drawn. Some environmental toxins, such as β-methylamino- l -alanine (BMAA) produced by cyanobacteria cause misfolding and aggregation of various proteins (Dunlop et al, 2013).…”
Section: Clinical and Neuropathological Criteria For Ad Diagnosismentioning
confidence: 99%
“…Air pollution exposure especially damages the BBB in the brainstem and can trigger an autoimmune response contributing to the neuroinflammatory and AD pathology present in children from very large urban centers (Calderón-Garcidueñas et al, 2015; Brockmeyer and D’Angiulli, 2016). Even though numerous studies connect specific metals and metalloids with Aβ and tau pathology (e.g., Aβ spontaneously self-aggregates in the presence of divalent metals like Fe, Cu, and Zn into amyloid fibrils, Mandel et al, 2007), recently bringing a “metal hypothesis of AD” into focus (Bush and Tanzi, 2008; Bush, 2013; Singh et al, 2014), such data remain rather controversial, warranting further investigations until convincing conclusions might be drawn. Some environmental toxins, such as β-methylamino- l -alanine (BMAA) produced by cyanobacteria cause misfolding and aggregation of various proteins (Dunlop et al, 2013).…”
Section: Clinical and Neuropathological Criteria For Ad Diagnosismentioning
confidence: 99%
“…Different approaches involving 2D-QSAR, 3D-QSAR, docking and statistics methods, were discussed as protocols that could provide essential information on the structural requirement for ligand binding to AChE. [71] A summary on molecular drug targets and therapies for Alzheimer's disease appeared in 2014, the authors [72] documented all the possible targets with known inhibitors for AD treatment. They [72] reiterated that computational approaches are rapidly applicable in drug design and development with appreciable efficiency.…”
Section: Computational-based Inhibitor Design For Cholinesterase: An mentioning
confidence: 99%
“…The major neuronal death and synaptic loss which is observed in the brain regions responsible for cognitive fuctions of AD is histopathologically characterized , includes the entorhinal cortex, ventral striatum, the cerebral cortex and hippocampus (Gupta et al, 2010). There are two hypothesis which have been proposed for pathophysiology and etiology studies of Alzheimer disease: the first hypothesis refers to the neurodegeneration of amyloid cascade whereas the second hypothesis refers to the malfunction of the cholinergic system which contains metal-mediated toxicity, tau aggregation and inflammation ( According to the neurodegeneration of amyloid cascade hypothesis, Alzheimer disease attars to begin with the proteolytic cleavage of the amyloid precursor protein (APP) and it also results in the production, aggregation, and the deposition of amyloid plaques and β-amyloid (Aβ) (Singh et al, 2014, Cummings et al, 2016.…”
Section: Alzheimer Disease Pathophysiologymentioning
confidence: 99%
“…The γ-secretase enzyme may be a potentially attractive drug target because it has an important role in the production of Aβ fragments by creating peptides of various lengths, namely Aβ40 and Aβ42 (Singh et al, 2014). It comprises of a molecular complex which has four integral membrane proteins namely:nicastrin, presenilin (PSEN), PEN-2 and APH-1 (Singh et al, 2014, Ahmad and J, 2013).It has been observed that NSAID analogues preferentially inhibit Aβ formation and it does not affect the Notch processing and other developments; so these NSAID analogues may be serve as a lead for optimizing the biological activity or starting point for future drug development against AD (Singh et al,2014).…”
Section: γ-Secretasementioning
confidence: 99%
See 1 more Smart Citation